Family’s Knowledge About Traditional Medication For Cholesterol Sufferers - Ade Irma Triana Siregar (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Cholesterol is one of the precusors for another steroid compound inside the body, for example corticosteroid, sex hormone, bile acid, and vitamin D. cholesterol is synthesized inside the body from Acetyl-CoA established meyalonate through a complex track. Indonesia as a country with the 4th highest number of cholesterol sufferers in the world after China, India, and United States of America and expected will increase become 21,3 million sufferers in 2030. The design used in this research is descriptive quantitative. This design was done to know the level of family’s knowledge about traditional medication for cholesterol sufferers in Mawar village, Selesai sub-district, Langkat district. The sample of this research used Stratified Random sampling technique. The sampling technique is using by purposive sampling technique where the sample selection by using choose the sample among populations according to what the researcher wants (purpose or problems in the research) (Notoatmodjo, 2014). Based on the research which has done to 23 respondents basically family’s knowledge about traditional medication for cholesterol sufferers in Mawar village, Selesai sub-district, Langkat district. From 23 respondents found that the majority of respondent which has sufficient knowledge about 11 people (47,8%), sufficient knowledge about 3 people (13,1%), well knowledge about 9 people (39,1%).